Patronage Factors and the Behavior of Customers towards Islamic Banking in Nigeria - omoruyi Aigbovo (Airlangga International Journal of Islamic Economics and Finance, 2022)
In this study, the selection criterion for Islamic banking in Nigeria was examined. Thus, the study investigates whether variables like; rate of return, Islamic teaching, bank’s reputation and service quality account for why customers patronize Islamic bank (Jaiz bank) in Nigeria. The general behavior of customers towards Islamic banking in Nigeria was also investigated.  A survey research design was adopted and all the customers of Jaiz bank branch in Herwa Gana Ward, Commercial Area of Gombe Local Government Area constitute the population of the study. A suitable sample of 60 respondents was the study's focus. The respondents were chosen using a convenient sampling strategy. 52 of the 60 administered surveys were deemed to be valid. The data were examined using simple percentages, descriptive statistics, correlation, and regression. It was discovered that in Nigeria, customers' attitudes toward Islamic banking are significantly influenced by the rate of return, Islamic principles, and bank reputation. In order to draw in more clients, the study advises Jaiz Bank to build upon its positive reputation and enhance the quality of its services. They can also promote the religious traditions in their advertisements to attract customers who are motivated to benefit from interest free banking services.